Collaborative Management to Reduce Intracranial High Pressure in Patients in the Intensive Care Unit (ICU) - Cecep Eli Kosasih; Anita Setyawati; Nisrina Nabila Heryana; Tati Sumarni; Tjong Veren Veronica (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Intracranial pressure is pressure in the head cavity which if increased will cause several problems, these include disturbances in cerebral perfusion pressure and cerebral blood flow. The purpose of this study was to find out how collaborative nursing interventions deal with the increase in ICT in the ICU. The study used a scoping review and article search approach using the PRISMA guidelines and the Cochrane handbook. The article search strategy uses keywords identified based on the PCC framework consisting of ICU patients (population); collaborative nursing intervention (concept); and increased intracranial pressure (context). The keywords used are “intensive care unit patient” OR “ICU patient” AND “collaborative nursing intervention” AND “increased intracranial pressure” OR “ICP”. The total search results for articles in databases PubMed, EbscoHost, SpringerLink, and academic searching engine Google Scholar. After doing this, it was found that 9 articles were used, and contained 5 types of intervention, namely head up with an elevation angle, mechanical ventilation, osmotherapy, hypothermia, and hypertonic saline. The five interventions were found to be effective in reducing ICP for patients treated in the ICU.